الحداثةُ بين الفكرِ الغربيّ والفكرِ العربيّ انقطاعٌ أو اتِّصال؟ الأدب أنموذجاً - رائد جميل عكاشة; خالد عبد الرؤوف الجبر (International Institute of Islamic Thought, 2014)
يعالج البحث إشكالية المثاقفة بين الفكر الغربي والفكر العربي، وتجسّد ذلك في التماهي مع التجربة الغربية في مسألة الحداثة بشكل عام والأدب بشكل خاص. لقد اعترى عملية المثاقفة خلل في عدم الوعي بالاختلافات البنيوية والمعرفية بين النظام المعرفي الغربي والنظام المعرفي العربي الإسلامي، مما أدّى إلى إسقاط تجربة الحداثة الغربية على الواقع العربي، دون الوعي بمفهوم الخصوصية. وكَشَف البحث عن العلاقة المَرَضية بين الحداثيين والتراث، مما أسهم في القطيعة شبه التامّة مع تراث الأمة، فضلاً عن انحياز الحداثيين إلى مفهوم التجاوز دون المرور بمرحلة الاستيعاب، مما أنتج لغة منبتة عن ذاتها. This paper addresses the problem of acculturation between Western thought and Arab thought, as manifested in the attempt to identify with the Western experience of modernity in general and literature in particular. This process of acculturation has experienced a defect caused by the lack of awareness of structural and epistemological differences between the Western and Arab-Islamic epistemologies. The experience of Western modernity has been projected on Arab reality without awareness of the uniqueness of both. This study reveals the pathological relationship between Arab modernists and Arab heritage, which resulted in almost total break with that heritage, especially in the modernists' attempt to hastily move forward, bypassing the necessary assimilation process, which resulted in producing language uprooted from itself and its civilizational context.